Triaxial accelerometer sensor trials for bat swing interpretation in cricket - Sarkar, A. K.; James, D. A.; Busch, A. W.; Thiel, D. V. (Procedia Engineering, 2011)
Analysis of bat swing is important to the assessment and understanding of effective batting in cricket. The key features of a bat swing include the spatio-temporal position of the bat before contact with the ball and the bat velocity. The current methods of bat swing analysis such as video tracking and coach observation are labor intensive and expensive. This work examined the use of small, low-cost, three dimensional motion sensors as a replacement to existing methods. Using two bat-mounted accelerometer sensors, two experiments were conducted: a set of ball-free, straight drives by an amateur batter at nominal constant speed, and a set of straight drives at different speeds by the same batter accompanied by video tracking. In all cases the bat swing was in the x-z plane of the sensors placed on the reverse face of the bat. The bat face remains in the z direction. The objective was to minimize accelerations perpendicular to the swing plane. Data analysis revealed consistent acceleration profiles with minimal acceleration perpendicular to the plane of the swing (x-z plane). The time lag between the z acceleration peak and the x acceleration peak is related to the speed of the bat. The highest peak in x acceleration results from the higher centrifugal force with minimum radius of gyration while the bat was close to the batter (confirmed by the video footage). This is the dominant rotational component plus an additional gravitational force in the x direction when the bat is aligned to gravity. The sensor attached to the on-side edge of the bat showed higher peak magnitude in x acceleration compared to that from the off-side edge, which indicated variation between the two edges of the bat during swing. The tilted position of the stationary bat at the start of each swing was determined from the x and z axis profiles from minus one g and zero respectively. Different peak accelerations were evident for different swing intensities. This study indicated that the accelerometer sensors can provide reliable bat swing information.